MODULLI TA’LIM TEXNOLOGIYASI ASOSIDA BO‘LAJ’AK MUSIQA O’QITUVCHILARINING KASBIY KOMPETENTLIGINI TAKOMILLASHTIRISH - Omanqulova, Sh.N. (SCIENCE and SOCIETY, 2019)
The article deals with modular learning technologies, the importance of their use in the higher education system, and the improvement of professional competence of future music teachers.
Keywords: modules; modular learning technologies; music education; teaching activity; technology; competence; professional competence; future teacher